2014
DOI: 10.1210/en.2013-1734
|View full text |Cite
|
Sign up to set email alerts
|

Central Adiponectin Acutely Improves Glucose Tolerance in Male Mice

Abstract: Adiponectin, an adipocyte-derived hormone, regulates glucose and lipid metabolism. It is also antiinflammatory. During obesity, adiponectin levels and sensitivity are reduced. Whereas the action of adiponectin in the periphery is well established the neuroendocrine role of adiponectin is largely unknown. To address this we analyzed the expression of adiponectin and the 2 adiponectin receptors (AdipoR1 and AdipoR2) in response to fasting and to diet-induced and genetic obesity. We also investigated the acute im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Interestingly, when cells were overexposed to insulin and adiponectin, the insulin-dependent Akt and ERK1/2 phosphorylations were totally restored. This agreed with previous studies demonstrating an adiponectin-dependent improvement of both hypothalamic and peripheral insulin sensitivity (27,31). Importantly, the insulin-sensitizing effects of adiponectin were abolished in APPL1-suppressed SH-SY5Y cells, presenting the first evidence for the critical role of APPL1 in neuronal adiponectin/insulin cross talk and in mediating the insulin-sensitizing effect of adiponectin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, when cells were overexposed to insulin and adiponectin, the insulin-dependent Akt and ERK1/2 phosphorylations were totally restored. This agreed with previous studies demonstrating an adiponectin-dependent improvement of both hypothalamic and peripheral insulin sensitivity (27,31). Importantly, the insulin-sensitizing effects of adiponectin were abolished in APPL1-suppressed SH-SY5Y cells, presenting the first evidence for the critical role of APPL1 in neuronal adiponectin/insulin cross talk and in mediating the insulin-sensitizing effect of adiponectin.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have reported that adiponectin is crucially involved in hypothalamic control of energy homeostasis (29,30). Additionally, central adiponectin improves glucose tolerance and reverses hypothalamic inflammation and insulin resistance in obese mice (31,32). These data demonstrate that the insulin-sensitizing properties of adiponectin are at least partially related to a neuroendocrine mechanism that involves central action of adiponectin.…”
mentioning
confidence: 63%
“…Recent in vivo studies have uncovered beneficial effects of adiponectin treatment on metabolic function. In male mice fed HFD, intracerebroventricular administration of adiponectin led to improved glucose homeostasis and reduced inflammatory signaling (Koch et al ., 2014). The increase in adiponectin levels has been well established in long‐lived mice such as Ames dwarf (Wang et al ., 2006), Snell dwarf (Brooks et al ., 2007) and GHR‐KO (Berryman et al ., 2004) mice.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data demonstrate that BMP8B acts by decreasing AMPK in VMH neurons connected to the LHA through glutamatergic fibers that stimulate the orexin (OX) system which in turn activate the SNS promoting thermogenesis in BAT and WAT [81]. Conversely, adiponectin (ADP) and resistin (RSTN) caused a decrease in BAT thermogenesis by activation of hypothalamic AMPK [85], [86], [87], [88], [89], [90], [91], although the role of the VMH in these actions remains unproven. Additional peripheral signals that act on the hypothalamus eliciting sympathetic firing to BAT and activating thermogenesis include amylin and uroguanylin (UGN), with UGN also inducing browning of WAT [92], [93], [94].…”
Section: The Hypothalamus: the Beginning Of The Travelmentioning
confidence: 99%